Knowledge, Attitudes, and Practices of Pulmonary Tuberculosis Patients Regarding Tuberculosis and Home-Based Treatment - Xuwen Fu; Jianjie Jiang; Yuanying Li; Jiajia Duan; Zhaojing Shi; Xiang Li (Healthcare, 2026)
Objectives: To assess the knowledge, attitudes, and intended practices (KAP) of pulmonary tuberculosis (PTB) patients regarding the disease and home-based treatment. Methods: A cross-sectional study was conducted at the authors’ hospital from 1 September 2024 to 28 February 2025, using a self-designed KAP questionnaire. Differences in KAP scores across demographic subgroups were analyzed, and the associations among knowledge, attitude, and practice were examined. Results: A total of 509 valid responses were included (effective rate: 90.73%). Participants were predominantly male (56.6%) and rural residents (68.0%). Their mean (SD) knowledge, attitude, and intended practice scores were 26.20 (2.90) (possible range: 15–30), 32.09 (4.14) (possible range: 9–45), and 35.89 (5.57) (possible range: 8–40), respectively. Correlation analysis showed significant but relatively weak positive correlations between knowledge and attitude (r = 0.257, p < 0.001), knowledge and intended practice (r = 0.136, p = 0.002), and attitude and intended practice (r = 0.251, p < 0.001). Multivariate logistic regression revealed that knowledge score (OR = 1.098, p = 0.007) and attitude score (OR = 1.094, p < 0.001) were independently associated with better intended practice. Living in rural areas (OR = 0.633, p = 0.043) and being government/enterprise/public institution staff (OR = 0.386, p = 0.004) were independently associated with lower intended practice scores. Conclusions: These findings highlight that higher levels of knowledge among PTB patients are positively associated with more favorable attitudes and better anticipated self-management practices. These associative findings generate the hypothesis that targeted educational interventions, especially among populations with lower education levels or non-urban backgrounds, might improve expected home-based treatment adherence, which warrants validation in future longitudinal studies.